The Effect of Sweet Potato Starch Concentration as Edible Coating on Quality of Minimally Processed Snake Fruit During Storage - Rizki Annisa; Ismed Suhaidi; Lasma Nora Limbong (Jurnal Rekayasa Pangan dan Pertanian, 2016)
The objective of this research was to find out the effect of starch concentration and storage time on quality of minimally processed snake fruit coated with edible coating. Method used in this research was completely randomized design (CRD) with 2 factors, namely the concentration of starch (P) : (2%, 3%, 4%, 5%, and 6%) and  storage time (L) : (2 days, 4 days, and 6 days). Parameters analyzed were weight loss, total acid, vitamin C content, total soluble solid, tanin content, total microorganism, organoleptic values of color, taste, flavor, and texture score. The results showed that the starch concentration  had highly significant effect on weight loss, total acid, vitamine C content, and total soluble solid. Storage time had highly significant effect on weight loss, total acid, vitamine C content, total soluble solid, tanin content, total microorganism, organoleptic values of color, taste, flavor and texture score. The interaction of two factors had highly significant effect on weight loss and total soluble solid and had significant effect on total acid and vitamine C content. The starch concentration of 5% with storage time 4 days could better protect the quality of minimally processed snake fruit. Keywords : edible coating, snake fruit, storage time, sweet potato starch